The Effect of Gap Width on Premixed Flame Propagation in Non-adiabatic Closed Hele–Shaw Cells. Issue 13 (3rd October 2022) - Huo, Jiepeng; Su, Hang; Jiang, Liqiao; Zhao, Daiqing; Li, Xing; Wang, Xiaohan
ABSTRACT: The premixed flame propagation with conductive heat loss in millimeter-scale narrow closed cells of different gap widths is investigated experimentally and numerically. The flame evolution is observed in a disc-shaped cell of which the width is varied from 2.0 mm to 5.0 mm. A non-monotonic relation between the flame propagation velocity and the gap width is found. Time-dependent numerical results exhibit good agreement with the experimental data and indicate that the flame behaviors are highly sensitive to the gap width. Since gap downsizing leads to significant heat loss and viscous friction from the wall, the propagation velocity will drop to almost laminar flame speed halfway for 2.0 mm width. For larger gaps, the flame propagation velocity is determined by the combined effect of the flame straining and the conductive heat loss. The former increases the flame front area while the latter strongly weakens the flame distortion. The trade-off of them yields the non-monotonic relation and an optimal width of 3.0 mm.